(untitled) (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Blowfish is a 64-bit block cipher with variable key length. The algorithm consists of two part: Key expansion and data encryption. Allowing its use in cryptography. In general, cryptography is about constructing and analyze communication protocols that can block an opponent. Various aspects of information security, Such as confidential data, Data integrity, Authentication and non repudance Is the center of modern cryptography. This case implementation with encryption and decryption techniques on audio files using java programming, aims to secure the audio data contained in it can be maintained and can only be read by user who have the cryptographic key.